PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN (STUDI KASUS KARYAWAN BAGIAN KANTOR PADA PT. AGUNG AUTOMALL PEKANBARU) - Nurul Laily; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study aimed to analyze the transformational leadership style and commitment organiasasi and its influence on employee performance of the office at PT. Agung Automall Harapan Raya, Pekanbaru. Transformational leadership style as a variable (X1), organizational commitment as a variable (X2), and employee performance as a variable (Y). The method in this research is descriptive and quantitative using SPSS 16, wherein the samples used are employees of the office is 37 done by census and data collection through questionnaires. The results of the analysis using the validity, reliability, determination test, simple linear regression, multiple linear regression test, t test and F. It can be concluded that the transformational leadership style have a significant effect on employee performance of the PT. Agung Automall Harapan Raya, organizational commitment significantly influence employee performance of the PT. Agung Automall Harapan Raya, and transformational leadership style and, organizational commitment significant effect on employee performance of the PT. Agung Automall Harapan Raya.Keywords: Transformational Leadership Style, Organizational Commitment and Employee Performance